Endohedral metallofullerenes-filled fullerene derivatives towards multifunctional reaction center mimics - Rudolf, Marc; Wolfrum, Silke; Guldi, Dirk Michael; Feng, Lai; Tsuchiya, Takahiro; Akasaka, Takeshi; Echegoyen, Luis (Chemistry - A European Journal, 2012)
In recent years, endohedral metallofullerenes have attracted tremendous interest not only in physics and chemistry, but also in interdisciplinary areas, such as materials and biological sciences. In this concept article we highlight recent results on different endohedral metallofullerenes based on lanthanides and their derivatives. The chemical and excited state reactivities of endohedral metallofullerenes are discussed for various endohedral clusters. Most important is the part that covers spectroscopic and kinetic assays of reductive and oxidative charge transfer evolving from photoexcited electron donors and electron acceptors, respectively, in a variety of electron donor-acceptor conjugates. Towards this end, we refer to the applications of endohedral metallofullerenes in photovoltaic devices that feature greater efficiency than devices fabricated with empty fullerenes. Herein, we focus mainly on results obtained in the groups of Akasaka, Echegoyen, and Guldi. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.